Building construction site surveying & development - Bishara, Joseph N.; Ullrich, Doug R.,|d1964-.; Grant, Ron.; Creative Educational Video, Inc. (Lubbock, TX CEV Multimedia, 2003)
Learn about basic masonry, basic site evaluation, site surveying and site development.
Site evaluation: factors to consider in site 1-4 (25 min.) ?Building construction: basic surveying (40 min.) ?Building construction: basic site development.
Includes: quizzes and finals; DVD-ROM content includes outlines, activities, printable quizzes and more.
Originally produced in 2003.
This disc is a recorded DVD and may not play in all DVD players or drives.
Producers, Joseph Bishara, Carrie Miller.
Host, Doug R. Ullrich, Jr.; narrator, Ron Grant.
DVD-R.
Keywords: Surveying; Building sites; Video discs